ASMA YAUM AL-QIYAMAH FIZ AL-QUR'AN AL-KARIM MIN KHILAL AL-MANZHIR AL-DALALI AL-MA'RIFI WA QIYAMUHU AL-TARBAWIYAH AL-RIHIYAH - Kosim, Abdul; Nur, Tajudin; Wahab, T. Fuad; Wahya, Wahya (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This study aimed to discuss the names of judgment day in the Qur'an through cognitive semantic approach and the values of spiritual education. Through the cognitive semantic approach, the conception of meaning to describe the judgment day in the Qur'an was formulated by mapping the meaning resulted from the source domain (Sd) to target domain (Sd). To show and compare references in (Sd) to (Td), referential technique was used. From organizing (Sd) to (Td) on metaphorical expressions which showed the judgment day in the Qur'an, the conceptions of the meaning of state, time, movement, and change were generated. The studies on the names of judgment day in the Qur'an influence the value of moral education, which is able to increase faith in God, observe nature and its big symptoms, create good character between God and man, and believe in God's noble character.